Knowledge, Attitude and Practice of Type 2 Diabetic Patients Regarding Obesity: Study in a Tertiary Care Hospital in Bangladesh - Saleh, Farzana (J Public Health Africa, 2012)
Prevention and management of obesity largely depends on patient motivation and education and these, in turn, can be greatly facilitated by adequate baseline data on the knowledge, attitude and practice (KAP) of patients. The aim of this study is to assess KAP on obesity among Bangladeshi type 2 diabetics. Under a cross-sectional design 160 type 2 diabetics were selected from outpatient department of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine & Metabolic Disorders. A standard questionnaire was constructed in local language and interview was administrated. Age and body mass index (BMI) of the respondents were 45.17±5.68 years and 25.6 ±4 kg/m(2) respectively. Among them 45% were male, 38% had primary education, 25% belonged to normal weight, 1/2 of them were overweight and rest were obese. KAP score of the respondents was [mean ±SD(%)] 60.03±13.82, 79.30±8.27, 55.50±19.21 respectively. Majority were unaware about ideal body weight, energy requirement and the weight measurement techniques. A substantial proportion of the respondents considered fast food, soft drinks, mayonnaise as healthier food. Majority of them positively agreed on willingness to follow proper diet, maintaining ideal body weight, dietary management and exercise. More than half of the normal weight and overweight respondents did exercise >45 min, while 1/3 obese did not do exercise (35%). KAP score were significantly associated with respondents’ level of education (P=0.0001, P=0.007, P=0.05 respectively) practice score was significantly associated with sex (P=0.0001), occupation (P=0.003) and BMI (P=0.0001). There is a need for increased effort towards developing and making education programs focusing on empowering the persons to transform their knowledge and attitude into practice.